2021
DOI: 10.1371/journal.pone.0255368
|View full text |Cite
|
Sign up to set email alerts
|

Application of endocrine biomarkers to update information on reproductive physiology in gray whale (Eschrichtius robustus)

Abstract: Most of our knowledge on reproductive biology of gray whales dates back to scientific research conducted during commercial whaling in the late 1950s and 1960s. The goal of the present study was to provide updated insights on reproductive physiology of gray whales, using progesterone and testosterone as biomarkers. We measured hormone concentrations using enzyme immunoassay (EIA) techniques in blubber biopsies collected from 106 individual whales from March to November over a span of 12 years (2004–2016) betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…Testosterone (3 ng/g) was detected only in one unsexed calf, ER-18-31, at a similar concentration reported for a juvenile gray whale male using LC/MS methodology (Hayden et al, 2017) but greater than mean concentrations observed at any life stage in gray whale males using immunoassays (Melica et al, 2021). No adult males were analyzed at the 50 mg ww mass, and our sample set did not include any breeding adult males, known in gray whales and other species for expressing higher concentrations (Boggs et al, 2019;Galligan et al, 2019;Melica et al, 2021).…”
Section: Gray Whale Blubber Hormone Profilessupporting
confidence: 74%
See 3 more Smart Citations
“…Testosterone (3 ng/g) was detected only in one unsexed calf, ER-18-31, at a similar concentration reported for a juvenile gray whale male using LC/MS methodology (Hayden et al, 2017) but greater than mean concentrations observed at any life stage in gray whale males using immunoassays (Melica et al, 2021). No adult males were analyzed at the 50 mg ww mass, and our sample set did not include any breeding adult males, known in gray whales and other species for expressing higher concentrations (Boggs et al, 2019;Galligan et al, 2019;Melica et al, 2021).…”
Section: Gray Whale Blubber Hormone Profilessupporting
confidence: 74%
“…Additionally, 17α-hydroxyprogesterone (13.8-39.8 ng/g, mean 26.76 ng/g) was detected in higher concentrations in both an adult female, ER-18-34 (13.8 ng/g) and an unsexed calf, ER-18-33 (39.8 ng/g) than in free ranging, live-captured, or stranded bottlenose dolphins (< 0.1-3.16 ng/g, Boggs et al, 2017;0-4.64 ng/g, Galligan et al, 2019;1.6-13.7 ng/g, Galligan et al, 2020) and humpback whales (< 0.5-1.87 ng/g, Dalle Luche et al, 2019). Testosterone (3 ng/g) was detected only in one unsexed calf, ER-18-31, at a similar concentration reported for a juvenile gray whale male using LC/MS methodology (Hayden et al, 2017) but greater than mean concentrations observed at any life stage in gray whale males using immunoassays (Melica et al, 2021). No adult males were analyzed at the 50 mg ww mass, and our sample set did not include any breeding adult males, known in gray whales and other species for expressing higher concentrations (Boggs et al, 2019;Galligan et al, 2019;Melica et al, 2021).…”
Section: Gray Whale Blubber Hormone Profilessupporting
confidence: 55%
See 2 more Smart Citations
“…For bottlenose dolphins, Boggs et al (2019) and Galligan et al (2020) have both reported elevated androgen concentrations in blubber from pregnant animals. Elevated concentrations of androgens and/or androgen metabolites during pregnancy have been reported in North Atlantic right whales (Eubaleana glacialis, Hunt et al, 2006;Corkeron et al, 2017), beluga (Richard et al, 2017), Yangtze finless porpoise (Neophocaena asiaeorientalis, Hao et al, 2006), blue whales (Balaenoptera musculus, Melica et al, 2021b) and humpback whales (Hunt et al, 2019) but were not observed in gray whale (Eschrichtius robustus) blubber (Melica et al, 2021a). Dalle Luche et al (2020) suggest that, during late term humpback whale pregnancy, A4 and T measurements may be more effective pregnancy biomarkers than P4.…”
Section: Introductionmentioning
confidence: 96%